Green Human Resource Management: Integrating Sustainability into Talent Development and Retention - Resti Yulistria; Willy Cahya Sundara; Eva Marsusanti; Vera Agustina Yanti (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
In the face of global environmental challenges and rising sustainability demands, organizations are increasingly adopting Green Human Resource Management (GHRM) to align human resource practices with environmental goals. This study explores how GHRM practices influence talent development and talent retention through the mediating roles of green organizational culture, green work engagement, and personal norms. Drawing on Resource-Based View (RBV) and Social Exchange Theory (SET), the research utilizes a quantitative design involving 110 respondents from multiple industries in emerging economies. Data were analyzed using Structural Equation Modeling (SEM-PLS), and the results reveal that GHRM significantly enhances both talent development and employee retention, mediated by employee engagement and green culture. Moreover, leadership commitment was found to strengthen the effect of GHRM on sustainability-driven talent strategies. These findings highlight that environmentally oriented HR practices not only advance ecological performance but also nurture a sustainable and motivated workforce. The study contributes theoretically by integrating GHRM, sustainability, and talent management into a unified framework, and provides practical implications for HR managers seeking to embed green competencies, strengthen commitment, and improve retention among sustainability-minded employees.